2017
DOI: 10.3126/njh.v14i1.17188
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic valve thrombosis in a tertiary cardiac centre

Abstract: Background and Aims: Prosthetic valve thrombosis remains a major complication of valve replacement surgeries in Nepal. A number of patients present with thrombotic complications mainly due to poor anticoagulation status with irregular INR checkup at the remote areas of Nepal. Thrombolysis is the preferred method in the management of stuck valve patients due to financial issues . We aimed to retrospectively study the clinical profile and management trends of stuck prosthetic valveMethods: A one year retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
5
0
2
Order By: Relevance
“…Further, majority (68.75%) of the patients were in the NYHA class I and II, 87.5% patients had subtherapeutic anticoagulation (INR < 1.6 in 14 patients) and showed a significantly decreased transvalvular gradient (P < 0.05) after TT. Few studies have reported 69-75% rate of inadequate anticoagulation and 2 - 3 times more prevalence of mitral valve vs. aortic valve thrombosis [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Further, majority (68.75%) of the patients were in the NYHA class I and II, 87.5% patients had subtherapeutic anticoagulation (INR < 1.6 in 14 patients) and showed a significantly decreased transvalvular gradient (P < 0.05) after TT. Few studies have reported 69-75% rate of inadequate anticoagulation and 2 - 3 times more prevalence of mitral valve vs. aortic valve thrombosis [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…In the series by Durrleman et al, they reported the maximum number of patients were in class III or IV at presentation (87%) [16]. Similarly in the study published by Gupta et al, reported that 46.4% of patients were in NYHA class III and 24.5 % of patients were in NYHA class IV at the time of presentation [18].…”
Section: Discussionmentioning
confidence: 93%
“…The majority of studies have cited sub-therapeutic INR as a major risk factor for the development of PVT which was mainly due to irregular follow-up and poor treatment compliance. Studies from India show variable rates of inadequate anticoagulation ranging from 41.5 To 90.3% [18][19][20]. Egbe et al found inadequate anticoagulation in 48% of patients with PVT [21].…”
Section: Discussionmentioning
confidence: 99%
“…66.6%of our patients showed complete response to thrombolysis. 76.2% and77.5% of patients showed complete response to thrombolytic therpy in studies conducted by Nawale et al Kathirvel et al [18] [26].…”
mentioning
confidence: 96%
See 1 more Smart Citation